Three-dimensional tooth morphology in patients with tooth agenesis and its association to agenesis pattern, severity, and sex - Chihiro Tanikawa; Miyuki Nakamura; Takashi Yamashiro (Scientific Reports)
Abstract Non-syndromic tooth agenesis (TA) can affect both the size and shape of teeth and may interact with sex. This study aimed to advance our understanding of tooth developmental mechanisms by constructing a multifactorial model integrating 3D dental morphology, TA patterns, severity, and sex differences. Digital dental models of 255 Japanese individuals (control: 187; TA: 68) were analyzed. We assessed the contributions of size and shape to sex- and TA-related differences in maxillary central incisors (UI) and first molars (UM) using surface distance mapping and a tooth agenesis-associated shape difference (TAShD) analysis. Additionally, permutation tests were conducted to evaluate the relationship between sex- and TA-associated morphological variation. TA patterns were further classified using k-means clustering, and their associations with 3D tooth morphology were examined. Surface distance maps revealed TA-related morphological traits in both UI and UM, including generalized size reduction, altered cingulum morphology, and diminished distolingual cusps. The TAShD analysis indicated that TA and sex independently influenced tooth shape, although both contributed to size variation. Three distinct TA patterns were identified: Cluster 1 (premolar agenesis) exhibited size reduction without significant shape changes; Cluster 2 (incisor and canine agenesis) showed alterations in both the size and shape of the UI; and Cluster 3 (agenesis of canines, premolars, and second molars) presented with size reduction and shape abnormalities, particularly in the UM. These morphological distinctions across clusters reflect the independent effects of TA and sex on the dental morphology. Collectively, these findings highlight the presence of distinct TA patterns and their associated shape characteristics, thereby offering novel insights into the multifactorial nature of tooth development.